Isolation and Characterization of Cellulose from Golden Melon (Cucumis melo L.) Fruit Peel Using Microwave-Assisted Extraction - Nurul Fadilah; Henny Purwaningsih; Tetty Kemala (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2026)
Golden melon (Cucumis melo L.) peel represents a promising source of cellulose derived from agricultural by-products. This study aimed to identify a favorable NaOH concentration for cellulose isolation using microwave-assisted extraction (MAE), as well as to evaluate the resulting cellulose in terms of yield, composition, and crystallinity. The extraction was conducted at 450 W using NaOH concentrations of 4%, 8%, and 10%. A relatively high cellulose yield (41.87 ± 0.16%) was obtained with 8% NaOH, accompanied by improved purity, as indicated by the relatively high cellulose content (76.51%) and low lignin content (8.47%). Fourier Transform Infrared (FTIR) analysis confirmed the presence of characteristic cellulose functional groups along with a reduction in lignin-related peaks. X-ray diffraction (XRD) analysis indicated increased crystallinity after treatment, with crystallinity indices of 52.5%, 51.8%, and 40.3% for 4%, 8%, and 10% NaOH, respectively. SEM analysis of the 8% NaOH sample showed a rough and porous morphology, likely associated with the removal of non-cellulosic components. These findings suggest that MAE is a potentially effective approach for cellulose isolation from golden melon peel, with 8% NaOH representing a favorable condition within the studied parameters based on a balance of yield, purity, and crystallinity.